Sustainable Finance and Green Investment: Policy Frameworks and Implementation Challenges - Joseph E. Stiglitz Muller (PT. Islamic Research Publisher, 2025)
Sustainable finance and green investment have emerged as strategic instruments for accelerating low-carbon economic transformation and achieving long-term sustainable development. Despite the growing adoption of environmental, social, and governance (ESG) principles, the implementation of sustainable finance policies remains constrained by regulatory fragmentation, institutional capacity, financial literacy, and investment risk perceptions. This study aims to analyze the effectiveness of sustainable finance policy frameworks, examine the practical challenges encountered during implementation, and identify institutional strategies that strengthen the integration of green investment into national development agendas. This research employed a qualitative field research design using a multiple-case study approach. Data were collected through semi-structured interviews with policymakers, financial institution executives, green investment practitioners, corporate sustainability managers, and academic experts, complemented by field observations and document analysis of sustainable finance regulations, policy reports, and institutional guidelines. The data were analyzed using thematic analysis involving data reduction, coding, categorization, interpretation, and triangulation to ensure the credibility and consistency of findings. The results demonstrate that the effectiveness of sustainable finance policies depends not only on regulatory quality but also on institutional coordination, transparent governance, standardized ESG reporting, and stakeholder collaboration. The study further reveals that inconsistent policy implementation, limited green financial instruments, insufficient technical expertise, and weak monitoring mechanisms continue to impede the mobilization of sustainable investment. However, digital financial innovation, public-private partnerships, green tax incentives, and enhanced sustainability disclosure significantly improve investor confidence and facilitate green capital allocation. The findings contribute to the literature by proposing an integrated policy implementation framework that combines regulatory coherence, institutional readiness, market incentives, and governance accountability as complementary drivers of sustainable finance. This framework offers practical guidance for governments, financial regulators, and investment institutions seeking to strengthen green finance ecosystems while supporting climate resilience, inclusive economic growth, and long-term sustainable development.